Celebrating Adam Watkins First Birthday in Watkins' Backyard - Watkins, Howard::::::::: (1979)
Doug Jones, Dave Brodie, Gerre Gurland-Jones, Fran Calloway seated at table Portable television and folding metal chairs in background